A COMPARATIVE DETERMINATION OF BARRIERS OF ORAL ENGLISH LEARNING FACED BY PREPARATORY YEAR STUDENTS - Al Asmari, AbdulRahman (European Scientific Journal, ESJ, 2015)
It has been reported that Saudi students are unable to achieve desired English language proficiency in general and oral skills in particular. This study is an attempt to investigate Saudi preparatory year students (SPYS) and English language teachers at English language center, Taif University to identify the barriers that hinder oral proficiency. The participants were 142 Saudi EFL learners and 47 English language teachers who responded to a self-developed Likert-scale questionnaire. The results of this empirical study have revealed that SPYS face issues in oral proficiency though they generally have positive attitudes towards speaking skills. They strongly agree that it is an important skill to continue their studies at tertiary level. There are several factors that contribute towards this situation that need immediate attention by the faculty as well the administration. It has been found out that attitudes of SPYS towards English language, frequent use of their mother tongue not only outside the campus but also inside the classroom with their peers and teachers, their inability to command proper pronunciation, appropriate grammatical structures, necessary vocabulary items, their hesitance to use the target language in front of their class fellows because of their fear of making mistakes etc. are major oral barriers. The results of this study did not reveal any significant oral barriers in relation to the behavior of English language teachers, English textbooks as well as English contact hours. Relevant suggestions have been forwarded that have significant implications not only for SPYS but also for English language teachers and PYD administration.